First record of Tulostoma exasperatum (Agaricaceae, Agaricales) in Mexico - Hernández Navarro, Eduardo (Instituto de Ecología, A.C., 2023)
Background and Aims: The genus Tulostoma groups species that are characterized by their angiocarpic basidiomes with a spore-sac possessing an apical mouth or ostiole and a well-defined stipe. Worldwide, 173 species are known, and 49 species have been cited in Mexico. One of the few species in the genus with lignicolous habit is T. exasperatum, which, in combination with its morphological traits, makes it a distinctive species. The aim of this work is to present T. exasperatum as a first record for Mexico.Methods: The material was collected in “Las Maravillas de Acahuato” ranch, Apatzingán municipality, Michoacán state, Mexico. The specimen was characterized macro and microscopically by in situ photographs, polarized light microscopy, light microscopy and scanning electron microscopy. Identification was carried out with specialized literature. Studied material is deposited in the macromycetes collection of the National Herbarium (MEXU) of the Biology Institute of Universidad Nacional Autónoma de México.Key results: Tulostoma exasperatum is recorded for the first time in Mexico, based on Mexican specimens. The species is distinguished by its exoperidium with reddish-brown conical to pyramidal verrucae that, when detached, leave lattice-like marks on the endoperidium, fimbriate ostiole, and winged reticulate basidiospores. In addition, its lignicous habit is characteristic, in soils rich in organic matter.Conclusions: Tulostoma exasperatum presents pantropical distribution. The morphology of the pigmented cells of the exoperidium warts is a poorly studied source of taxonomic information. The catalog of species of the genus Tulostoma in Mexico is raised to 50 species, and the number of gasteroid Agaricomycetes in Michoacán is raised to 38 species.